2007
DOI: 10.1111/j.1742-7843.2007.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Rosiglitazone, a Peroxisome Proliferator‐Activated Receptor‐γ Ligand, and NMDA Receptor Antagonist (MK‐801) on Experimental Embolic Stroke in Rats

Abstract: Peroxisome proliferator-activated receptor-γ (PPAR-γ ) agonists have been found to have potent anti-inflammatory actions and suggested as potential therapies for brain ischaemia. Glutamate is the most common excitatory neurotransmitter in the central nervous system and is released excessively during ischaemia. Stroke therapy will require combinations of drug classes, because no single drug class has yet been proven efficacious in human beings. The present study was conducted to assess whether N-methyl-d -aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…PPARs have also been shown to attenuate adaptive immune responses by inhibiting helper T cell functions and by mediating apoptosis of B cells [41, 42]. PPARs are activated by naturally ocurring fatty acid derivatives, eicosanoides, and by synthetic pharmacological agents, such as fibrates (PPAR α ) and glitazones (PPAR γ ) [18, 22, 43]. PPAR ligands have been shown to exert anti-inflammatory activities in various cell types by inhibiting the gene expression for proinflammatory cytokines, metalloproteinases, and hepatic acute-phase proteins.…”
Section: Biological Functions Of Pparsmentioning
confidence: 99%
“…PPARs have also been shown to attenuate adaptive immune responses by inhibiting helper T cell functions and by mediating apoptosis of B cells [41, 42]. PPARs are activated by naturally ocurring fatty acid derivatives, eicosanoides, and by synthetic pharmacological agents, such as fibrates (PPAR α ) and glitazones (PPAR γ ) [18, 22, 43]. PPAR ligands have been shown to exert anti-inflammatory activities in various cell types by inhibiting the gene expression for proinflammatory cytokines, metalloproteinases, and hepatic acute-phase proteins.…”
Section: Biological Functions Of Pparsmentioning
confidence: 99%
“…To compensate for the effect of brain oedema, the corrected infarct volume was calculated as follows: corrected infarct area = measured infarct area 9 {1À[(ipsilateral hemisphere area-contralateral hemisphere area)/contralateral hemisphere]}. Brain oedema was determined using the following formula: oedema = (volume of left hemisphere volume of right hemisphere)/volume of right hemisphere [21]. The brain oedema was reported as percentages.…”
Section: Methodsmentioning
confidence: 99%
“…RSG, an agonist of peroxisome proliferator-activated receptor-gamma (PPARγ), has been demonstrated to be effective in the treatment of ischemic stroke [28,29]. There are a few studies that have reported the role of RSG in the treatment of ICH [19,30], thus demonstrating that RSG promotes hematoma resolution, decreases neuronal damage, and improves functional recovery.…”
Section: Introductionmentioning
confidence: 99%